Inflation Dynamics and Long-Run External Shocks in a Highly Import-Dependent Economy: Evidence from Laos Using VAR/VECM - SIVONGXAY, KHAMFONG; Fan, Zuojun (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study analyzes the determinants of inflation in Laos, focusing on the roles of the exchange rate, import values, and dollarization. A Vector Error Correction Model (VECM) is employed to examine both long-run and short-run relationships. The results show that exchange-rate movements have a strong long-run impact on consumer prices: a 1% depreciation of the LAK leads to an approximate 1.10% increase in prices. Rising import values also exert upward pressure on inflation, while greater dollarization helps mitigate price pressures over time. In the short run, most variables are not statistically significant, although the system converges to its long-run equilibrium at a speed of 27.6% per quarter. Impulse Response Function (IRF) results indicate that exchange rate and import shocks generate persistent upward pressure on prices over a 12-quarter horizon, whereas dollarization has only a limited effect. Forecast Error Variance Decomposition (FEVD) shows that external factors-particularly the exchange rate and import values-account for approximately 70% of inflation fluctuations in the medium to long run. Overall, the findings suggest that external factors are the dominant drivers of inflation dynamics in Laos. While short-run effects remain limited, these results provide important policy implications for maintaining price stability in a highly import-dependent economy.